"...he's going to be facing the same things that he faced prior to being locked up": perceptions of service needs for substance use disorders - Sara Beeler; Tanya Renn; Carrie Pettus (BMC, 2023)
Abstract Background High rates of substance use disorders (SUDs) exist among justice-involved populations (i.e., persons incarcerated or recently released). SUD treatment is crucial for justice-involved populations as unmet treatment need increases reincarceration risk and impacts other behavioral health sequalae. A limited understanding of health needs (i.e. health literacy) can be one reason for unmet treatment needs. Social support is critical to seeking SUD treatment and post-incarceration outcomes. However, little is known about how social support partners understand and influence SUD service utilization among formerly incarcerated persons. Methods This mixed method, exploratory study utilized data from a larger study comprised of formerly incarcerated men (n = 57) and their selected social support partners (n = 57) to identify how social support partners understand the service needs of their loved ones recently released from prison who returned to the community with a diagnosis of a SUD. Qualitative data included 87 semi-structured interviews with the social support partners covering post-release experiences with their formerly incarcerated loved one. Univariates were conducted on the quantitative service utilization data and demographics to complement the qualitative data. Results Majority of the formerly incarcerated men identified as African American (91%) averaging 29 years of age (SD = 9.58). Most social support partners were a parent (49%). Qualitative analyses revealed that most social support partners avoided using or did not know the language to use regarding the formerly incarcerated person's SUD. Treatment needs were often attributed to focus on peer influences and spending more time at their residence/housing. Analyses did reveal that when treatment needs were recommended in the interviews, social support partners reported employment and education services to be most needed for the formerly incarcerated person. These findings align with the univariate analysis with their loved ones reporting employment (52%) and education (26%) as their most reported service utilized post-release, compared to only 4% using substance abuse treatment. Conclusion Results provide preliminary evidence suggesting social support partners do influence the types of services accessed by formerly incarcerated persons with SUD. The findings of this study emphasize the need for psychoeducation during and after incarceration for individuals with SUDs and their social support partners.